‘Why Do You Ask?’ The Nature and Impacts of Attitudes towards Public Opinion Surveys in the Arab World - Justin J. Gengler (14634960) (2019)
For the first time in an Arab country, this article examines attitudes toward public opinion surveys and their effects on survey-taking behavior. The study uses original survey data from Qatar, the diverse population of which permits comparisons across cultural–geographical groupings within a single, non-democratic polity. The authors find that Qatari and expatriate Arabs hold positive views of surveys, both in absolute terms and relative to individuals from non-Arab countries. Factor analysis reveals that the underlying dimensions of survey attitudes in Qatar mostly mirror those identified in Western settings, but a new dimension is discovered that captures the perceived intentions of surveys. Two embedded experiments assess the impact of survey attitudes. The results show that generalized attitudes toward surveys affect respondents’ willingness to participate both alone and in combination with surveys' objective attributes. The study also finds that negative views about survey reliability and intentions increase motivated under-reporting among Arab respondents, whereas non-Arabs are sensitive only to perceived cognitive and time costs. These findings have direct implications for consumers and producers of Arab survey data.  Other information Published in: British Journal of Political Science License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1017/S0007123419000206